Analysis of teacher readiness implementing Kurikulum Merdeka in Informatics at Pelita Nusantara - Samsul Maarip Aripin (Inovasi Kurikulum, 2026)
Rapid technological advancements in the globalization era have driven curriculum reform in Indonesia, including the Kurikulum Merdeka, which emphasizes learner-centered education and 21st-century skills through the Informatics subject in elementary schools. This study aims to analyze teacher readiness in implementing Kurikulum Merdeka at Pelita Nusantara Elementary School and to identify challenges and effective strategies. The study is significant for understanding the readiness of Informatics teachers, who require specialized technological skills and computational understanding, given that they are relatively new to teaching this subject. Employing a descriptive qualitative approach, the research involved in-depth interviews with Informatics teachers and observations at Pelita Nusantara School. Findings indicate that Informatics instruction remains at a basic level, dominated by a teacher-led instructional approach and limited use of digital media. Key challenges include inadequate ICT infrastructure, a lack of specialized training, and student behavior issues. These results underscore the importance of hands-on technical training, ICT infrastructure upgrades, and strengthened school-level collaboration to ensure the successful implementation of Kurikulum Merdeka in the Informatics subject.   Abstrak Perkembangan teknologi yang pesat di era global mendorong reformasi kurikulum di Indonesia, termasuk Kurikulum Merdeka yang menekankan pembelajaran berpusat pada peserta didik dan keterampilan abad ke-21, melalui Mata Pelajaran Informatika di sekolah dasar. Penelitian ini bertujuan untuk menganalisis kesiapan guru dalam mengimplementasikan Kurikulum Merdeka di SD Pelita Nusantara serta mengidentifikasi tantangan dan strategi yang efektif. Urgensi studi ini adalah untuk memahami kesiapan guru Informatika yang memerlukan keterampilan teknologi khusus dan pemahaman komputasional mengingat mereka relatif baru mengampu mata pelajaran ini. Menggunakan pendekatan kualitatif deskriptif, penelitian ini melibatkan wawancara mendalam dengan guru Informatika serta observasi di Sekolah Pelita Nusantara. Temuan menunjukkan bahwa pembelajaran Informatika masih pada tingkat dasar, didominasi oleh pendekatan instruksional, dengan pemanfaatan media digital yang terbatas. Tantangan utama meliputi keterbatasan infrastruktur TIK, ketiadaan pelatihan khusus, serta perilaku murid. Hasil ini menegaskan pentingnya pelatihan teknis langsung, peningkatan infrastruktur TIK, serta penguatan kolaborasi di tingkat sekolah untuk keberhasilan implementasi Kurikulum Merdeka pada Mata Pelajaran Informatika. Kata Kunci: kesiapan guru; Kurikulum Merdeka; pembelajaran Informatika; pendidikan dasar